Honour-based Abuse in England and Wales: Who Does What to Whom? - Bates, Lis (2017)
The British Government defines honour-based abuse as “a crime or incident which has, or may have been, committed to protect or defend the honour of the family and/or community”. Policy has increasingly responded to specific forms of honour-based abuse, particularly forced marriage, but little scrutiny has been given to who and what are involved in other forms. This empirical study investigated the nature and profile of cases known to police and victims’ NGOs in England and Wales; in particular, whether and how they differed from forced marriage, and other domestic and intimate partner abuse. Data were collected from 162 case files identified as honour-based abuse by a police force and two victims’ NGOs, and combined with 1,312 case profiles from a national charity. Descriptive thematic analysis of the 162 case summaries was used to compare and contrast groups of cases on different characteristics, and quantitative methods (descriptive statistics and logistic regression) were used to test all 1,474 cases for significant associations between key variables relating to victims, perpetrators, and forms of abuse. A typology of honour-based abuse was developed, based on the relationship(s) of the victim and perpetrator, number of perpetrators, and characteristics of the individuals and abuses involved. The three types were: (Type I) Partner abuse; (Type II) Family abuse; and (Type III) Partner plus family abuse. I argue that, within an overarching lens of gender-based violence, Types I and III can be seen as forms of domestic and intimate partner abuse; whereas Type II is different in nature. Until further research is conducted to validate my proposed typology, I suggest that the three types continue to be conceptualised together as honour-based abuse. To this end, I propose a revised policy definition, which incorporates the three types and better reflects these findings. Advancement of new empirical data to address the knowledge gap around who and what are involved in honour-based abuse, development of a typology, and proposal of a new policy definition, all make this study a unique and original contribution to knowledge